Analisis Spasial Pengaruh Alokasi Ruang dan Pola Kepemilikan Lahan terhadap Konversi Lahan Sawah: Studi Kasus Kecamatan Rajeg: Spatial Analysis the Effect of Spatial Patterns and Land Ownership Status on Paddy Field Conversion: A Case Study of Rajeg District - Afan Ray Mahardika; Baba Barus; Didit Okta Pribadi (P4W LPPM IPB, 2021)
Tangerang Regency is one of the regencies in Banten Province, which has a fairly established agricultural system with fertile land potential for the agricultural sector. The central government has prioritized the regenciy’s rice field are as one of the food barns of Indonesia. Rajeg District is one of nine districts in Tangerang Regency that has been designated as a food barns. Land conversion has been a threat in implementing stable and sustainable food security. Significantly, conversion of paddy fields can affect the availability of food and inventory of rice fields. The purpose of this study is to analyze the spatial pattern of land use change conversion using the Landscape Metrics method. Data used in this research are secondary data, including land use maps of 2005, 2012, and 2018, spatial pattern maps of Tangerang Regency Spatial Plan (RTRW) 2011-2031, and maps of land ownership status in Rajeg District. Result of the analysis shows that the largest conversion of land use change occurs in paddy fields into developed land in agricultural areas with unregistered land ownership status (not registered and not certified). The characteristic of spatial pattern of this conversion type covers a wide conversion area with various forms of conversion geometry. Patch density tends to cluster (not fragmented). The built-up land formed in this type of conversion tends to be massive and in the form of clusters.